A multiplex fluorescence-based loop-mediated isothermal amplification assay for identifying chicken parvovirus, chicken infectious anaemia virus, and fowl aviadenovirus serotype 4. Issue 2 (4th March 2023) - Fan, Qing; Xie, Zhixun; Zhang, Yanfang; Xie, Zhiqin; Xie, Liji; Huang, Jiaoling; Zeng, Tingting; Wang, Sheng; Luo, Sisi; Li, Meng
ABSTRACT: Chicken parvovirus (ChPV), chicken infectious anaemia virus (CIAV) and fowl adenovirus serotype 4 (FAdV-4) are avian viruses that have emerged in recent years and have endangered the global poultry industry, causing great economic loss. In this study, a multiplex fluorescence-based loop-mediated isothermal amplification (mLAMP) assay for detecting ChPV, CIAV and FAdV-4 was developed to simultaneously diagnose single and mixed infections in chickens. Three primer sets and composite probes were designed according to the conserved regions of the NS gene of ChPV, VP1 gene of CIAV and hexon gene of FAdV-4. Each composite probe was labelled with a different fluorophore, which was detached to release the fluorescence signal after amplification. The target viruses were distinguished based on the colour of the mLAMP products. The mLAMP assay was shown to be sensitive, with detection limits of 307 copies of recombinant plasmids containing the ChPV target genes, 749 copies of CIAV and 648 copies of FAdV-4. The assay exhibited good specificity and no cross-reactivity with other symptomatically related avian viruses. When used on field materials, the results of the mLAMP assay were in 100% agreement with those of the previously published PCR assay. The mLAMP assay is rapid, economical, sensitive and specific, and the results of amplification are directly observable by eye. Therefore, the mLAMP assay is a useful tool for the clinical detection of ChPV, CIAV and FAdV-4 and can be applied in rural areas.